2021
DOI: 10.1016/j.heliyon.2021.e07399
|View full text |Cite
|
Sign up to set email alerts
|

Effect of salt stress on proximate composition of duckweed (Lemna minor L.)

Abstract: The shortage of conventional feedstuff is one of the rising issues faced by the developing countries of the world. To bridge the gap between supply and demand of the major feedstuff it is desirable to practice the use of nonconventional feed resources. Duckweeds are the aquatic macrophytes growing in stagnant water bodies that offer a choice to be used as an alternate feed. Before the use of any alternate feed, it is vital to know the nutritional composition of the feed under diverse environmental conditions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…The content in Lemna varies from 23 to 59%, and Spirodela contains 8% carbohydrates (Figure 3C). The highest report from Lemna minor (59%) was calculated based upon the difference of a total content with mineral content, protein, and lipids [64]. A similar report was made by Zhao et al (2014) with 51.2%, although the carbohydrate content seems to include the cell wall content [65].…”
Section: Isoleucine (% Protein) I Leucine (% Protein) J Lysine (% Protein) K Methionine (% Protein) L Phenylalanine (% Protein) M Serine mentioning
confidence: 71%
“…The content in Lemna varies from 23 to 59%, and Spirodela contains 8% carbohydrates (Figure 3C). The highest report from Lemna minor (59%) was calculated based upon the difference of a total content with mineral content, protein, and lipids [64]. A similar report was made by Zhao et al (2014) with 51.2%, although the carbohydrate content seems to include the cell wall content [65].…”
Section: Isoleucine (% Protein) I Leucine (% Protein) J Lysine (% Protein) K Methionine (% Protein) L Phenylalanine (% Protein) M Serine mentioning
confidence: 71%
“…Proteins and lipids content in duckweeds could easily change adjusting with the environmental conditions in which they lived. A study conducted by Yu et al 18 showed that the proteins content reached 0.34 g gG 1 of dry weight, it can be concluded that cultivation conditions became one of the trade-offs for gaining high proteins and lipids content.…”
Section: Resultsmentioning
confidence: 99%
“…It is closely related to the plant life cycle and can reflect the dynamic relationship between root growth and water supply [80,81]. Studies on maize [82] and duckweed [83] show that the root activity of plants decreases or increases first and then decreases under drought stress. In this experiment, the root activity of tomato seedlings grown under an ebb-and-flow irrigation system was significantly higher than those irrigated with top sprinkle irrigation, maintaining vigorous metabolic activity and indicating that the water supply of EFI treatment was more uniform, and the effects of drought and other uneven water changes caused by TSI treatment were reduced.…”
Section: Discussionmentioning
confidence: 99%